PENGAMBILAN KEPUTUSAN UNTUK MEMILIH MINUMAN DENGAN METODE WEIGHT PRODUCT (WP) DI KOTA MATARAM - Muhammad Imam Dinata; Muhammad Rizkillah; Arif Rahman (Program Studi Informatika Universitas Teknologi Sumbawa, 2023)
One of these micro-enterprises is a coffee shop. The number of coffee shops in the Mataram city area is currently approximately 50 coffee shops. Many forms and choices of drinks sell in coffee shops make buyers confused when choosing which beverage product to consume. Necessary to decide to choose beverage products with a Decision Support System Using the Weighted Products order to assist in the selection of beverages when placing an order at a coffee shop that suits the needs of buyers. Only 2 basic types of drinks are usually ordered at coffee shops, namely coffee, and milk. Produce the best alternative sequence used for decision-making. the decision to choose drinks in the city of Mataram using the Weighted Product (WP) with several criteria, namely price, composition, type of drink, and size. From the results of calculations carried out the type of coffee milk drink obtained the highest value, namely 0.016, then for the second rank the type of long black drink with a value of 0.0157, and third rank, the type of avocado milkshake drink with a value of 0.015.